Ethanol Oxidation Reaction Catalyzed by Palladium Nanoparticles Supported on Hydrogen‐Treated TiO2 Nanobelts: Impact of Oxygen Vacancies. Issue 9 (27th June 2017) - Lu, Bingzhang; Yao, Bin; Roseman, Graham; Deming, Christopher P.; Lu, Jia En; Millhauser, Glenn L.; Li, Yat; Chen, Shaowei
Abstract: Nanocomposites based on palladium nanoparticles deposited onto TiO2 nanobelts were prepared by chemical reduction of Pd(II) precursors and the catalytic activity towards ethanol oxidation reaction (EOR) was examined and compared within the context of TiO2 oxygen vacancies formed by thermal annealing at controlled temperatures (400–600 °C) in a hydrogen atmosphere. Transmission electron microscopic measurements showed that the Pd nanoparticles (about 5 nm in diameter) were clustered somewhat on the surfaces of hydrogen‐treated TiO2 nanobelts (Pd/hTiO2 ), but distributed rather evenly on the untreated ones (Pd/TiO2 ). X‐ray photoelectron spectroscopic studies suggested electron transfer from Ti to Pd in the Pd/hTiO2 samples, as compared to untreated Pd/TiO2, due to the formation of oxygen vacancies in TiO2 nanobelts where the concentration increased with increasing thermal annealing temperature, as evidenced in electron paramagnetic resonance measurements. Significantly, electrochemical measurements showed markedly enhanced EOR activity of both Pd/TiO2 and Pd/hTiO2 in alkaline media, as compared to commercial Pd/C, and the activity increased drastically with the concentration of oxygen vacancies, most likely because oxygen vacancies facilitated the formation of hydroxyl species on the TiO2 surface that played a critical role in the oxidation of ethanol to acetate. Abstract : Oxygen is key : Nanocomposites based on palladium nanoparticles supported on TiO2 nanobelts exhibit apparent electrocatalytic activity towards the ethanol oxidation reaction. The activity may be further enhanced by chemical reduction of the oxide substrates due to the formation of oxygen vacancies.